PBL Learning using Working Backward Strategies to Improve Mathematical Problem Solving Ability - Murniati, Siti; Mulyono, Mulyono; Kharis, Muhammad (Unnes Journal of Mathematics Education, 2017)
Tujuan penelitian ini untuk mengetahui rata-rata kelas dan ketuntasan klasikal kemampuan pemecahan masalah matematik siswa dengan pembelajaran PBL strategi working backward, perbedaan rata-rata kemampuan pemecahan masalah matematik siswa dengan pembelajaran PBL strategi working backward dan pembelajaran konvensional, dan penggolongan keterampilan proses siswa kelas VIII yang diajar dengan pembelajaran PBL strategi working backward. Dari populasi siswa kelas VIII SMP Negeri 1 Godong tahun pelajaran 2015/2016 terpilih siswa kelas VIII A sebagai kelas eksperimen dan siswa kelas VIII I sebagai kelas kontrol. Data diperoleh dengan metode dokumentasi, observasi, dan tes, kemudian data hasil tes dianalisis menggunakan uji rata-rata satu pihak, uji proporsi satu pihak, dan uji perbedaan rata-rata. Hasil penelitian menunjukkan bahwa rata-rata kelas dan kemampuan pemecahan masalah matematik siswa dengan pembelajaran PBL strategi working backward lebih dari KKM dan dapat mencapai ketuntasan klasikal, rata-rata kemampuan pemecahan masalah matematik siswa menggunakan pembelajaran PBL strategi working backward lebih baik daripada yang diajar dengan pembelajaran konvensional, dan hasil pengamatan keterampilan proses siswa diperoleh 10 siswa sangat terampil, 21 siswa terampil, dan 4 siswa cukup terampil. The purpose of this research was to find out the class average and classical completeness of students’ problemsolving ability in mathematics with PBL learning working backward strategy, different average the students’ problemsolving ability in mathematics with PBL learning working backward strategy and conventional teaching, and the classification eighth grade students’ process skills that are taught by PBL learning working backward strategy. From the population in this study were students of class VIII SMP Negeri 1 Godong in 2015/2016 academic year was elected students of class VIII A students as experimental class and students of class VIII I as the control class. Data obtained by the method of documentation, observation and tests, then data of test results was analyzed using one hand average analysis, the proportion of oneparty test, and test of different average. The results showed that the class average and students' problem solving ability in mathematics with PBL learning working backward strategy was more than minimum mastery criteria and reached the classical completeness, the average of students' problem solving ability in mathematics using PBL learning working backward strategy was better than who have been taught by conventional learning and the results of students skill observation obtained 10 students are highly skilled, 21 students are skilled student, and 4 students are skilled enough.